2011
DOI: 10.1159/000322740
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Long Spinal Cord Lesions and Anti-Aquaporin 4 Antibodies in Neuromyelitis Optica Patients in Taiwan

Abstract: Background and Objective: It was the aim of this study to determine the prevalence of anti-aquaporin 4 antibody (anti-AQP4 Ab) and long spinal cord lesions in neuromyelitis optica (NMO) and multiple sclerosis (MS) patients in Taiwan. Asia has a relatively high rate of NMO compared with MS patients. Anti-AQP4 Ab is an important marker for NMO worldwide, but serological data and clinical profiles of NMO patients in Taiwan have not been reported. Methods: This retrospective study compared the clinical symptoms, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 85 publications
(87 reference statements)
4
6
0
Order By: Relevance
“…Sensitivity and specificity values using the AQP4-Ab test alone (56.9 and 95.6%, respectively) were broadly similar to those reported previously [6,9,18,19,20,25,26,27,28,29,30,31,32]. For example, sensitivity and specificity values of 56 and 99% were reported in a Dutch cohort [29], while other studies have reported values of 71 and 91% in Chinese patients [26], 58 and 100% in Japanese patients [9], and 73 and 91% in patients from the USA [9].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Sensitivity and specificity values using the AQP4-Ab test alone (56.9 and 95.6%, respectively) were broadly similar to those reported previously [6,9,18,19,20,25,26,27,28,29,30,31,32]. For example, sensitivity and specificity values of 56 and 99% were reported in a Dutch cohort [29], while other studies have reported values of 71 and 91% in Chinese patients [26], 58 and 100% in Japanese patients [9], and 73 and 91% in patients from the USA [9].…”
Section: Discussionsupporting
confidence: 89%
“…For example, sensitivity and specificity values of 56 and 99% were reported in a Dutch cohort [29], while other studies have reported values of 71 and 91% in Chinese patients [26], 58 and 100% in Japanese patients [9], and 73 and 91% in patients from the USA [9]. Furthermore, AQP4-Ab seropositivity in NMO was 78% in Caucasian Germans [28], 68% in a mixed American cohort [27], 62% in Danes [6], 41% in Taiwan [30], 60% in Hong Kong [31] and 64% in Brazilians [32], suggesting ethnic differences, although these variations may also reflect differences in antibodies, test methods, and/or cutoff values. Three studies compared various assays for AQP4-Ab seropositivity and concluded that cell-based assays were superior to other methods, with sensitivities of 74-86% [18,19,20].…”
Section: Discussionmentioning
confidence: 97%
“…34.5%) was consistent with the relative low seroprevalence of AQP4 Ab in Asian patients with NMO (Matsuoka et al, 2007;Wang et al, 2011). Whereas increased plasma levels of TNF-a, IFN-c, and IL-17 might suggest specificity for NMO, these cytokines are affected by many inflammatory diseases and are associated with the severity of inflammation.…”
Section: Discussionsupporting
confidence: 68%
“…Aquaporin 4 (AQP4) antibody (AQP4 Ab/NMO-IgG), an antibody against a water channel protein, has recently been described as a diagnostic marker for NMO (Lennon et al, 2004). However, its sensitivity varies between studies, being particularly low for Asian patients (e.g., $40% of patients with NMO show positivity for AQP4 Ab in Taiwan compared to $60-70% in Western countries) (Matsuoka et al, 2007;Wang et al, 2011). Therefore, AQP4 is not an optimal marker for NMO.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, longitudinally extensive cord lesions were also seen more frequently in NMO than MS, that is, 72.4% versus 22.7%, P < 0.001 [ 15 ]. Studies from Thailand and Taiwan have demonstrated similar observations in their cohorts with LESCLs and seropositivity [ 16 , 17 ]. In fact, Wingerchuk et al found the presence of a longitudinally extensive cord lesion extending more than 3 vertebral segments to be the most reliable feature in the diagnosis of NMO [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 60%